Eksplorasi Keanekargaman herpetofauna di Kecamatan Girimulyo Kabupaten Kulon Progo Yogyakarta - Qurniawan, Tohy Febry; Addien, Fuad Uli; Eprilurahman, Rury; Trijoko, Trijoko (Sekolah Pascasarjana, UGM, 2012)
The research was aimed to reveal and document herpetofauna from Girimulyo District kulon progo Regency, Daerah Istimewa Yogyakarta Province. This reseach was done from November - Desember 2008 and January - April 2009 in faor research locations were Girimulyo, Jatimulyo, Giripuro and Purwosari. The VES (Visual Encaounter Survey) method were used and combined with interview method. A total of 40 species of herpetofauna are identifoed in to 13 family. Among 40 species, on;ly one (Mycrohyla achatina) is endemic to java. The commonest along all site were Eutropis multifasciata and Hylarana chalconota.